Bryophyte ecology and climate change - Tuba, Zoltan; Slack, Nancy G.; Stark, Lloyd R. (Cambridge ; Cambridge University Press, 2010)
'Bryophytes, especially mosses, represent a largely untapped resource for monitoring and indicating effects of climate change on the living environment. They are tied very closely to the external environment and have been likened to'canaries in the coal mine'. Bryophyte Ecology and Climate Change is the first book to bring together a diverse array of research in bryophyte ecology, including physiology, desiccation tolerance, photosynthesis, temperature and UV responses, under the umbrella of climate change. It covers a great variety of ecosystems in which bryophytes are important, including aquatic, desert, tropical, boreal, alpine, Antarctic, and Sphagnum-dominated wetlands, and considers the effects of climate change on the distribution of common and rare species as well as the computer modeling of future changes. This book should be of particular value to individuals, libraries, and research institutions interested in global climate change'--
'This book is dedicated to Zoltan Tuba. Its origin was a symposium entitled Ecological Responses of Bryophytes to Changing Climate. It was presented at the American Bryological and Lichenological Society (ABLS) meeting with the Botanical Society of America (BSA) in Chico, California in 2006. Nancy Slack, then president of ABLS, and Zoltan Tuba of Godollo University, Hungary, organized the symposium, which included speakers from many different countries. An editor at Cambridge University Press (England) saw the program on the Internet and asked the organizers to write a book on this subject. All the symposium speakers agreed to contribute chapters and subsequently others doing important work in this field were asked to join them'--
Machine generated contents note: List of contributors; Preface; Part I. Introductory Chapters: 1. The ecological value of bryophytes as indicators of climate change Nancy G. Slack; 2. Bryophyte physiological processes in a changing climate: an overview Zolt Tuba; Part II. Ecophysiology: 3. Climatic responses and limits of bryophytes: comparisons and contrasts with vascular plants Michael C. F. Proctor; 4. Effects of elevated air CO2 on bryophytes: a review Zolt Tuba, Edit $1-<|(Bv$1'Xu (Band IldikJ{u2BE3}s; 5. Seasonal and interannual variability of light and UV acclimation in mosses Niina M. Lappalainen, Anna Hyyryla;inen and Satu Huttunen; Part III. Aquatic Bryophytes: 6. Ecological and physiological effects of changing climate on aquatic bryophytes Janice Glime; 7. Aquatic bryophytes under ultraviolet radiation Javier Martinez-Abaigar and Encarnaci N{u2D64}nez-Oliver; Part IV. Desert and Tropical Ecosystems: 8. Responses of a biological crust moss to increased monsoon precipitation and nitrogen deposition in the Mojave desert Lloyd R. Stark, D. Nicholas McLetchie, Stanley D. Smith and Melvin J. Oliver; 9. Ecology of bryophytes in Mojave desert biological soil crusts: effects of elevated CO2 on sex expression, stress tolerance, and productivity in the moss Syntrichia caninervis Mitt. John C. Brinda, Catherine Fernando and Lloyd R. Stark; 10. Responses of epiphytic bryophyte communities to simulated climate change in the tropics Jorge J{u2863}ome, S. Robbert Gradstein and Michael Kessler; Part V. Alpine, Arctic, and Antarctic Ecosystems: 11. Effects of climate change on tundra bryophytes Annika K. Ja;gerbrand, Robert G. Bj$1'Xr(Bk, Terry Callaghan and Rod Seppelt; 12. Alpine bryophytes as indicators for climate change: a case study from the Austrian Alps Daniela Hohenwallner, Harold G. Zechmeister, Dietmar Moserm, Harald Pauli, Michael Gottfried, Karl Reiter and Georg Grabherr; 13. Bryophytes and lichens in a changing climate: an Antarctic perspective Rod D. Seppelt; Part VI. Sphagnum and Peatlands: 14. Living on the edge: the effects of drought on Canada's western boreal peatlands Melanie Vile, Kimberli D. Scott, Erin Brault, R. Kellman Wieder and Dale H. Vitt; 15. The structure and functional features of sphagnum cover of the northern west Siberian mires in connection with forecasting global environmental and climatic changes Aleksei V. Naumov and Natalia P. Kosykh; 16. The southernmost sphagnum-dominated mires on the plains of Europe: formation, secondary succession, degradation and protection Janos Nagy; Part VII. Changes in Bryophyte Distribution with Climate Change: Data and Models: 17. The role of bryophyte paleoecology in quaternary climate reconstructions Guszt{u2876} Jakab and P S$1!ZG(Begi; 18. Signs of climate change in the bryoflora of Hungary Tam P{u2BE3}s; 19. Can the effects of climate change on British bryophytes be distinguished from those resulting from other environmental changes? Jeffrey W. Bates and Christopher D. Preston; 20. Climate change and protected areas: how well do our rare bryophytes fare? Barbara J. Anderson and Ralf Ohlemuller; 21. Modeling the distribution of Sematophyllum substrumulosum (Hampe) E. Britton as a signal of climatic changes in Europe Ceci;lia Se;rgio, Rui Figueira and Rui Menezes; 22. Modelling bryophyte productivity across gradients of water availability using canopy form-function relationships Steven Rice, Nathali Neal, Jesse Mango and Kelly Black; Part VIII. Conclusions: 23. Bryophytes as predictors of greenhouse gas enrichment and current climate change L. Dennis Gignac; 24. Conclusions Nancy G. Slack and Lloyd R. Stark; Index.s
Includes bibliographical references and index.
Keywords: Bryophytes -- Climatic factors; Bryophytes -- Ecology